2015
DOI: 10.1089/tmj.2014.0088
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Quality Assessment Methods for Smartphone Health Apps

Abstract: This article provides a summary of currently used methods for assessing the quality of smartphone health-related apps and proposes a set of criteria to enable future studies to consistently review health-related app quality in a standardized manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
140
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(147 citation statements)
references
References 17 publications
1
140
0
4
Order By: Relevance
“…Quality and Risk of Bias Checklist for Studies That Review Smartphone Applications was used to ensure that methods for apps' review are adequately described [13].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quality and Risk of Bias Checklist for Studies That Review Smartphone Applications was used to ensure that methods for apps' review are adequately described [13].…”
Section: Methodsmentioning
confidence: 99%
“…Despite the wide distribution and popularity of health apps, many of them have been rapidly developed [13], and there is lack of evidence of their efficacy. For example, a meta-analysis published by Direito, Carraça [14] found only 7 randomized controlled trials (RCTs) evaluating app intervention for PA and/or sedentary behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study has several strengths, including a comprehensive search to identify all relevant BP tracking apps, a rigorous app assessment process based on best practices from the app evaluation literature, [22] and duplicate review of all apps by independent investigators. [22] Despite the strengths, there are several limitations.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…[22,23] It is important to assess app information consistency with best practice, which will help clinicians with app recommendations and ensure accurate, safe app use by patients. [22,24,25] Kumar et al recently described the functional characteristics and consumer interaction metrics for the top 107 hypertension-related apps for Apple iPhone and Google Android devices. [23] They reported that a majority of these are designed to track blood pressure, weight or, body mass index.…”
Section: Introductionmentioning
confidence: 99%